Intrusion Detection System Menggunakan Snort dan Telegram Sebagai Media Notifikasi - Danu Satin S; Wahyuddin Wahyuddin; Ahmad Kautsar; Agus Setyawan (Universitas Informatika dan Bisnis Indonesia, 2025)
Intrusion Detection System (IDS) is a device or mechanism designed to monitor, analyze, and detect suspicious activities within a network or computer system, protecting IT infrastructure from security threats such as cyberattacks and unauthorized access. Snort, as one of the IDS solutions, is capable of analyzing network traffic in real-time and detecting various threats, including buffer overflow, port scanning, and DoS attacks. This study employs a combination of hardware and software implemented in a computer network. Initial testing utilized Telegram Bot integration to deliver attack notifications, while the final testing evaluated Snort's capability to detect other types of attacks, such as DoS, FTP login, and port scanning. The results demonstrate that the Snort IDS effectively detects various types of attacks with different attacker operating systems, including Port Scan, Ping of Death, FTP, TCP Synflood, and Denial of Service attacks. These findings establish Snort as an essential solution for enhancing network security in the digital era.